Airborne radar evidence for tributary flow switching in Institute Ice Stream, West Antarctica: Implications for ice sheet configuration and dynamics. Issue 9 (3rd September 2015) - Winter, Kate; Woodward, John; Ross, Neil; Dunning, Stuart A.; Bingham, Robert G.; Corr, Hugh F. J.; Siegert, Martin J.
Abstract Despite the importance of ice streaming to the evaluation of West Antarctic Ice Sheet (WAIS) stability we know little about mid‐ to long‐term dynamic changes within the Institute Ice Stream (IIS) catchment. Here we use airborne radio echo sounding to investigate the subglacial topography, internal stratigraphy, and Holocene flow regime of the upper IIS catchment near the Ellsworth Mountains. Internal layer buckling within three discrete, topographically confined tributaries, through Ellsworth, Independence, and Horseshoe Valley Troughs, provides evidence for former enhanced ice sheet flow. We suggest that enhanced ice flow through Independence and Ellsworth Troughs, during the mid‐Holocene to late Holocene, was the source of ice streaming over the region now occupied by the slow‐flowing Bungenstock Ice Rise. Although buckled layers also exist within the slow‐flowing ice of Horseshoe Valley Trough, a thicker sequence of surface‐conformable layers in the upper ice column suggests slowdown more than ~4000 years ago, so we do not attribute enhanced flow switch‐off here, to the late Holocene ice‐flow reorganization. Intensely buckled englacial layers within Horseshoe Valley and Independence Troughs cannot be accounted for under present‐day flow speeds. The dynamic nature of ice flow in IIS and its tributaries suggests that recent ice stream switching and mass changes in the Siple Coast and Amundsen Sea sectors are not unique to these sectors, that they may have been regular during the Holocene and may characterize the decline of the WAIS.